Dinamika Sampradaya di Bali - I Gusti Putu Gede Widiana (Sphatika: Jurnal Teologi, 2022)
The topic of this paper is the phenomenon of sampradayas within Hinduism in Bali. Until now, very few social researchers have taken them into account. Therefore, I hope that I can disclose some important things related to social religious dynamics of the Balinese Hindu community since the appearance of sampradayas in the second half of the 20th century. The paper will explain the characteristics of three sampradayas, the response of Balinese Hindu to them, and their influence on the institution of Parisada and the institution of Desa Pekraman. The research is qualitative, using field observation, interviews with the respondents, participation in their activities, and collecting other important data. To understand the influence of sampradayas on the institution of Parisada and the institution of Desa Pekraman I collected information, which was reported and documented by the mass media. Then, I analyzed the data using the anthropology of religion’s theory. In the field  find the facts that the appearance of sampradayas have caused different perceptions among Balinese Hindus, which generally can be separated into three types: those who accept the sampradayas as a spiritual messenger; those who ignore the existence of sampradayas; and those who are suspicious about their appearance, that they would be harmful to the Balinese Hindu order, which is handed down from generation to generation. The culminating point of that rejection is that the government banned a sampradaya in 1984.